Reshaping of Shipping and Logistics in Smart, Green and Digital - Fausta Ari Barata (Budapest International Research and Critics University, 2021)
The modern market has specific achievements as well as modern infrastructure. One of them is to build a smart port, environmentally friendly, and digitalization. Digitalization is part of industry 4.0, and both of them become a threat, but give opportunities to change the business and make a business model make a change. The international market has grown speedily sea transportation to become an important part on delivery goods from other countries. Sustainability sea transportation is done by providing easy access, affordability, safety, economist, reliability, infrastructure with the concept of environmentally friendly and friendly transportation service. Nowadays the maritime logistics is to become attention for stakeholders in the logistic sector. The evolution of maritime logistics is as a new discipline has produced greater change, from increasing ping ship, increasing customer request, the changing of a support role on supply chain, and logistic. The delivery with environmentally-friendly lead to use resources and energy to transport the people and good with a ship and special attention on decreasing resources and energy to preserving global environment and environmental pollutants resulted by ship.